Solution‐Processed Perovskite/Metal‐Oxide Hybrid X‐Ray Detector and Array with Decoupled Electronic and Ionic Transport Pathways. Issue 8 (26th June 2022) - Jin, Peng; Tang, Yingjie; Xu, Xuehui; Ran, Peng; Wang, Yan; Tian, Yue; Huang, Yong; Zhu, Bowen; Yang, Yang (Michael)
Abstract: Lead halide perovskites possess heavy elements and excellent mobility‐lifetime ( µτ ) product, becoming desirable candidates for X‐ray detectors. However, current perovskite photoconduction detectors (PCDs) with vertical geometry, where electronic signals and mobile ions share the same conduction path, are facing with extremely challenging ion‐migration issue. Herein, a hybrid X‐ray detector device structure, in which perovskite is vertically stacked onto an indium oxide (In2 O3 ) transistor with lateral transport geometry is designed, perovskite mainly acts as X‐ray sensitizer to activate In2 O3 conduction channel, the actual electrical signal is conducted and collected in the lateral metal‐oxide device. With the decoupled ionic and electronic transportation, hybrid detectors are insensitive to the ionic motion of perovskite, hence demonstrating no hysteresis and almost no shifting of baseline that are often observed in PCDs, hybrid detectors also exhibit reduced dark current, improved response time, and four times higher photocurrent signals. Finally, array integration of hybrid detectors and preliminary X‐ray imaging is realized. The work provides an effective device strategy in addition to the mere material alternations to attain high‐performance perovskite‐based X‐ray detectors and arrays. Abstract : A device structure to decouple ionic and electronic transportation. A perovskite sensitizer is vertically stacked onto an indium oxide transistor with lateral transport geometry. Detectors are insensitive to the ionic motion of perovskite, hence demonstrating no hysteresis and almost no shifting of baseline that are often observed in photoconductors. Detectors also exhibit reduced dark current, improved response time, and four times higher photocurrent signals.